UPAYA MENINGKATKAN BELAJAR PKN MELALUI PENERAPAN MODEL NHT DI KELAS V SDN 050676 KEBUN BALOK - Zaitun . (Universitas Negeri Medan, 2016)
Abstract: Efforts To Improve Student Learning Outcomes Pkn Through Cooperative Learning Model Application Type NHT In Class V SDN 050676 Garden State Beam.This study aims to improve students' understanding of the material. The research subject of sixth grade students by the number of students as many as 13 people. Student activity data according to the second observation observer in the cycle I and II are Activities writing / reading (37.1%), working LKS (25.9%), asked their peers (13.5%), to ask the teacher (11.8 %), and are not relevant to KBM (11.8%). Activities of students in the second cycle of observation by both observers, among others: writing / reading (24.7%), Working LKS (49.9%), asked their peers (16.5%), ask the teacher (10.6%), and are not relevant to KBM (2.4% ). Keywords: Cooperative Learning type Numbered Heads Together, Learning Outcomes, Learning Activities Abstrak: Upaya Meningkatkan Belajar Pkn Melalui Penerapan Model Pembelajaran Kooperatif Tipe NHT Di Kelas V SDN 050676 Kebun Balok. Penelitian ini bertujuan untuk meningkatkan pemahaman siswa terhadap materi. Subjek penelitian siswa kelas VI dengan jumlah siswa sebanyak 13 orang. Data aktivitas siswa menurut kedua pengamatan pengamat pada siklus I dan II adalah Aktivitas menulis/membaca (37,1%), mengerjakan LKS (25,9% ), bertanya sesama teman (13,5%), bertanya kepada guru (11,8%), dan yang tidak relevan dengan KBM (11,8%). Aktivitas siswa pada Siklus II menurut pengamatan kedua pengamat antara lain: menulis/membaca (24,7%), Mengerjakan LKS (49,9%), bertanya sesama teman (16,5%), bertanya kepada guru (10,6%), dan yang tidak relevan dengan KBM (2,4%). Kata Kunci : Pembelajaran Kooperatif tipe Numbered Heads Together, Hasil Belajar Siswa, Aktivitas Belajar